Bifunctional electrode performance for zinc-air flow cells with pulse charging. (10th October 2017) - Pichler, Birgit; Weinberger, Stephan; Reščec, Lucas; Grimmer, Ilena; Gebetsroither, Florian; Bitschnau, Brigitte; Hacker, Viktor
Graphical abstract: Highlights: Manufacture of bi-catalyzed bifunctional air electrodes via scalable process. Direct synthesis of NiCo2 O4 on carbon nanofibers or nickel powder support. 450 charge and discharge cycles over 1000 h at 50 mA cm −2 demonstrated. Pulse charging with 150 mA cm −2 is successfully applied on air electrodes. Charge and discharge ΔV of <0.8 V at 50 mA cm −2 when supplied with O2. Abstract: Bifunctional air electrodes with tuned composition consisting of two precious metal-free oxide catalysts are manufactured for application in rechargeable zinc-air flow batteries and electrochemically tested via long-term pulse charge and discharge cycling experiments at 50 mA cm −2 (mean). NiCo2 O4 spinel, synthesized via direct impregnation on carbon nanofibers or nickel powder and characterized by energy dispersive X-ray spectroscopy and X-ray diffraction experiments, shows high activity toward oxygen evolution reaction with low charge potentials of < 2.0 V vs. Zn/Zn 2+ . La0.6 Sr0.4 Co0.2 Fe0.8 O3 perovskite exhibits bifunctional activity and outperforms the NiCo2 O4 spinel in long-term stability tenfold. By combining the catalysts in one bi-catalyzed bifunctional air electrode, stable performances of more than 1000 h and 450 cycles are achieved when supplied with oxygen and over 650 h and 300 cycles when supplied with synthetic air. In addition, the pulse charging method, which is beneficial for compact zinc deposition, is successfully tested on air electrodes during long-term operation. The oxygen evolution potentials during pulse, i.e. at tripled charge current density of 150 mA cm −2, are only 0.06–0.08 V higher compared to constant charging current densities. Scanning electron microscopy confirms that mechanical degradation caused by bubble formation during oxygen evolution results in slowly decreasing discharge potentials.